Poverty levels and children's health status: study of risk factors in an urban population of low socioeconomic level - Roberto M.S. Issler; Elsa R.J. Giugliani; Guilherme T. Kreutz; Clarice F. Meneses; Elisa B. Justo; Valerie M. Kreutz; Milton Pires (Revista de Saúde Pública, 1996)
To test the hypothesis that the low socioeconomic population living is shanty towns in Porto Alegre presents different levels of poverty which are reflected on its health status, a cross-sectional study was designed involving 477 families living in Vila Grande Cruzeiro, Porto Alegre, Brazil. The poverty level of the families was measured by using an instrument specifically designed for poor urban populations. Children from families living in extreme poverty (poorest quartile) were found to have higher infant mortality rate, lower birth weights, more hospitalizations, and higher malnutrition rates, in addition to belonging to more numerous families. Thus, the shanty town population of Porto Alegre is not homogeneous, and priority should be given to the more vulnerable subgroups.